Konsep Pendidikan Adab dalam Kitab Ta’lim al-Muta’allim Karya Imam Al-Zarnuji: Kajian Literatur: The Concept of Adab Education in the Book of Ta'lim al-Muta'allim by Imam al-Zarnuji: Literature Review - Abdurrahman, Abdurrahman; Nurwahida, Nurwahida; Samsuddin, Samsuddin (Litera Academica Publishing, 2024)
This research article aims to examine the concept of education in adab as presented in the book Ta'lim al-Muta'allim by Imam Az-Zarnuji. The method employed is a literature review, analyzing the concept of adab proposed by Imam Az-Zarnuji in Ta'lim al-Muta'allim. The results of the study reveal that adab, which includes sincerity of intention (adab towards Allah), discipline (adab towards oneself), respect for teachers (adab towards teachers), harmonious relationships with fellow students (adab towards peers), and respect for parents, plays a crucial role in supporting an effective learning process and shaping the noble character of students. The implications of this research provide both philosophical and practical foundations for educators, students, and educational institutions to instill the values of adab as an integral part of the education system.